1999
DOI: 10.1021/ac9902289
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Mass Shifts in Ion Trap Mass Spectrometry:  Experiments and Simulations

Abstract: Experimental data and simulations of trapped-ion motion are used to characterize the phenomenon of compound-dependent mass shifts in a quadrupole ion trap mass spectrometer. The ratio of axial to radial dimensions of the ion trap and the nature and pressure of the bath gas are identified as experimental variables which influence the chemical mass shift. Systematic changes in chemical shifts occur with changes in the chemical structure of the ion, for example between members of a homologous series of alkylbenze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 81 publications
6
70
0
Order By: Relevance
“…In the spectrum shown in 1a, a third prominent peak was observed at m/z ϳ762. This peak was unusually wide, with pronounced tailing to the low mass side and a significant chemical mass shift [39,40]. These observations are consistent with the formation of a weakly bound complex.…”
Section: Resultssupporting
confidence: 71%
“…In the spectrum shown in 1a, a third prominent peak was observed at m/z ϳ762. This peak was unusually wide, with pronounced tailing to the low mass side and a significant chemical mass shift [39,40]. These observations are consistent with the formation of a weakly bound complex.…”
Section: Resultssupporting
confidence: 71%
“…As a result, traditional rf amplitude sweeps have remained the favored method of ion trap operation. It is also theoretically possible to sweep the size of the device (r 0 ), but this is impossible in practice [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the nonlinear fields are regarded as the main factor in the degradation of the ion trap performance. For instance, the resultant nonlinear effects, such as ion delay ejection [31,32], nonlinear resonance [33,34], and frequency shift [35,36], are considered to be harmful to the mass resolution, sensitivity, and mass accuracy, respectively. With the in-depth study, the nonlinear fields have been found to be beneficial and have the potential to break the performance barrier and develop new operation modes of the ion trap.…”
mentioning
confidence: 99%